Pearl River Delta: Scales, Times, Domains: A Mapping Method for the Exploration of Rapidly Urbanizing Deltas - Xiong, Liang (A+BE | Architecture and the Built Environment, 2020)
An implemented design of an urban area not only imposes long-term conditions on societal processes, but also on natural processes. The urbanization of the Pearl River Delta (PRD) is a highly dynamic process that has interfered with many natural and artificial processes in the complex system. The involved human and natural processes, each with their own scale and speed of change, compose the complex urban delta landscape. The dominance of the efficiency-oriented fast urbanization process and its accompanying infrastructure development have put the deltaic social, cultural, and ecological environments at greater risk. Human activities have caused conflicts of a lack of cooperation with nature and coordination with other human activities during the rapid urbanization. The effectiveness of the related plans and designs depends on their capability to acknowledge and adapt to the nature of urban deltas. The research aims to provide an understanding of an urbanizing delta in which different scales, times, and domains are related to each other; and to examine how this understanding can be used in a planning and design process in a rapidly urbanizing delta. A mapping method is developed according to the key notions in the understanding of urban deltas, namely its systems, scales, and temporality. The systematic mapping approach was used to organize and analyze both short-term and long-term spatial data during the rapid delta urbanization processes by transforming spatial data via scales, times, and domains. The mapping approach works with insufficient data, which is often the case in a rapidly changing environment, to identify spatial challenges from a longterm perspective. Applied in the PRD, the knowledge of the development of the urban landscape had been inventoried, synthesized, and presented in its own spatial-temporal model using maps. Three types of processes (landscape formation, infrastructure extension, and urbanization) were identified according to their speeds. Spatial interactions were illustratively explained on both the delta scale and local scale from 4000 BC to the present with a time extent ranging from 2000 years to 50 years. The visualization revealed a transition of the regional pattern from a water-based mode to a land-based mode, during which an unawareness of the landscape and a detached urban pattern were developed. The present flooding issue was revealed by identifying the critical threshold signals, namely sudden changes in the spatial pattern of the dike system. Such trends increased the flood risk in the new urban areas on both the delta and regional scales. The mapping approach provided a probable vision of 2080, and a possible alternative vision. The two visions offered both the options of repair and transformation for the discussion of future planning and design. Both empirical and hypothetical mapping were deployed to provide a comprehensive understanding of the delta. Mapping served as a tool with which to not only represent existing knowledge, but also to seek missing knowledge. The intervention of this mapping framework was applied and evaluated in terms of design, decision-making, and education, and the insights gained were used to discover new possibilities and strategies for the delta. The systematic spatialization approach provided a spatial analysisbased design and planning alternative. In this approach, evidence-based arguments facilitated the cooperation and collaboration of professionals, stakeholders, and the interested public during the planning and design of the delta. During knowledge gathering and the re-mapping process, current stakeholders from different domains were able to collaborate, new stakeholders (the citizens) became involved, and enough awareness of natural processes was created to spur cooperation during the decision-making process. The systematic mapping across scales, time, and domains provided the stakeholders with a new mindset during design and planning, in which they were able to collaborate with each other and develop interventions that could cooperate with the natural process in the rapidly urbanizing delta. The mapping approach also directed possibilities of sustainable planning and design process by generating a circulation among the individual design, collective design, and mass awareness of the PRD. The mapping approach thus served as a vehicle that brought awareness to the spatial relationships, exchange of knowledge, and means of collaboration in both the short term and long term, on both small and large scales, and among different domains and stakeholders. This study contributes to the knowledge of urban delta planning and design from the following five aspects. (1) It extends the understanding of the differences and mutual influences of the urban and natural dynamics to the highest level by investigating the region with the fastest urbanization process in the past four decades. (2) It provides an approach for the analysis, understanding, and evaluation of the rapid change of urban dynamics on a large scale and with an extreme transition stage. (3) It enables the possibility of achieving a more effective, adaptive, and resilient strategy by providing an understanding of spatial knowledge. For the first time, the complexity and uncertainty of urban deltas and essential relationships (such as natural-human, land-water, and spatialmanagement relationships) on a substantial scale and with a rapid change of speed are explored. Furthermore, (4) this study devises, employs, and tests innovative visualization via multiple spatial and temporal scales. This is required to establish suitable interventions and measures via interactive communication and decision-making during the processes of design, planning, and management with stakeholders. Finally, (5) this study provides an effective data acquisition and analysis method to bypass the issues of data censorship, insufficiency, and inaccuracy in Chinese urban research. In other words, this study provides a strategy to achieve more integrated and resilient delta planning and design. It provides a substantial opportunity via visualization and spatialization to overcome the obstacle of localism among different levels of governments in the decision-making and implementation processes. It also helps to increase public awareness of, and participation in, the planning and design process, which are often lacking in the Chinese context.